Influence of “Not Too Young To Run” Campaign Social Media Messages on Youth Political Participation in Nigeria - Toyosi Khadijat Owoyale; Onaopepo Ibrahim Bamidele; Ojetola Adetola Afolabi; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
Today's generation of young people is the largest the world has ever known, half of the global population is under the age of 25, and young people between the ages of 15-25 constitute one-fifth of this total. Yet, young people are starkly underrepresented in government and politics at virtually every level. The